INCLUSION BODIES IN ORAL DISEASES – AN OVERVIEW - M, Parasakthi (Journal of Biomedical and Pharmaceutical Research, 2020)
The inclusion bodies are tiny particles found freely suspended and floating within the cytoplasmic matrix. Due to this, it is also called as cytoplasmic inclusions. These are formed with decreasing pH and from the pool of soluble fusion proteins within the cell. They are the elementary bodies, formed during infectious diseases or within the virus-infected cells such as rabies, herpes, measles, etc. Disease progression occurs with biochemical and cellular changes. Inclusion bodies are used in staging the diseases and aid in planning the treatment. This article aims to review the inclusion bodies in various oral lesions and their morphology.<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>